The effect of an Empowerment-Based Human Centered Educational Program on early weaning - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2021)
Aim: To determine the effects of an Empowerment-Based Human Centered Educational Program on early weaning. Background: Exclusive breastfeeding (EBF) means that the infant receives only breast milk during the first six months of life. It is essential for the healthy growth of the infants and is supported by the main health organizations all around the world. Intervention studies performed within the antenatal period suggest that the education extends the duration of breastfeeding and increases the frequency of EBF. Methods: This is a semi-randomized control study. An interactive training module including role-plays which contain traditional patterns, short films, short presentations, and group practice with models was prepared. The participants were recruited in the study based on the voluntary participation of pregnant women followed up for antenatal care in a total of four family health centers in Pendik, a district of Istanbul. The pregnant women of one center formed the control group while others constituted the intervention group. All of them were certified as Baby Friendly institution. A pretest and a posttest have been performed to measure breastfeeding knowledge in the intervention group. The mothers of the intervention group have been randomized into two subgroups: one group for reminder call and the other for routine follow-up. All the participants including control group were called at the end of the postpartum sixth month to determine the rates of EBF. Results: Statistically significant increase in the rates of EBF at the end of six months showed the effectiveness of the education module (42.9 versus 22.2%, P = 0.001). Supplementary food taking time was earlier in the control group (18.5 +/- 8 versus 15 +/- 9.5 week, P = 0.03). The main reason of early weaning reported by the mothers was the insufficiency of the mother's milk. Conclusion: The group training and postnatal reminders were found to be more effective than the individual training provided at the baby-friendly health institutions in terms of the effectiveness on increasing the frequency of EBF.
Keywords: breast milk; breastfeeding; education; BREAST-FEEDING EDUCATION; DURATION